1988
DOI: 10.1152/ajpendo.1988.255.6.e760
|View full text |Cite
|
Sign up to set email alerts
|

Role of interleukin 1 and tumor necrosis factor on energy metabolism in rabbits

Abstract: A study of the combined effects of intravenous infusion of the recombinant cytokines beta-interleukin 1 (IL-1) and alpha-tumor necrosis factor (TNF) on energy substrate metabolism in awake, conditioned, adult rabbits was performed. After a 2-h basal or control period, 48-h fasted rabbits were administered TNF and IL-1 as a bolus (5 micrograms/kg) followed by a continuous intravenous infusion (25 ng.kg-1.min-1) for 3 h. Significant increases in plasma lactate (P less than 0.01), glucose (P less than 0.01), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
37
0
3

Year Published

1991
1991
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 26 publications
1
37
0
3
Order By: Relevance
“…Increased glucose production and utilization are major features of the metabolic response to the infection ( 1,2,50). Previous studies demonstrated that administration of TNF causes hypoglycemia (51 ), and this finding has been partially explained by the fact that TNF increases glucose utilization both in vitro (52,53) and in vivo (51,54,55), although there are conflicting results (56). The most striking aspect of the response to TNF in our study is the similarity to the response to glucagon infusion.…”
Section: Discussionsupporting
confidence: 54%
“…Increased glucose production and utilization are major features of the metabolic response to the infection ( 1,2,50). Previous studies demonstrated that administration of TNF causes hypoglycemia (51 ), and this finding has been partially explained by the fact that TNF increases glucose utilization both in vitro (52,53) and in vivo (51,54,55), although there are conflicting results (56). The most striking aspect of the response to TNF in our study is the similarity to the response to glucagon infusion.…”
Section: Discussionsupporting
confidence: 54%
“…Possible explanations for this would include focal areas of ischemia that have been documented to occur in meningitis (29) but that would not be detected by measurement of total organ blood flow or humoral factors that would work in concert with ischemia to induce anaerobic metabolism. In other tissues, anaerobic glycolysis has been shown to be accelerated by humoral factors, including cytokines, resulting in increased glucose utilization and lactate production (30). This may be particularly relevant to the central nervous system in meningitis, where elevated cytokine levels have been measured in CSF and been found to be associated with poor outcome (13,17).…”
Section: Bacterial Titer Reduction (Log Cfu/h)mentioning
confidence: 99%
“…Tumor necrosis factor (TNF)' and IL-I induce hemodynamic shock in experimental animals (1)(2)(3)(4); the combined infusion of IL-I and TNF produces tissue damage and metabolic derangements similar to those associated with injury and sepsis in humans (3)(4)(5). Furthermore, serum TNF and IL-1,8 levels are elevated in patients with Gram-negative bacteremia, and correlate with severity ofthe sepsis (6).…”
mentioning
confidence: 99%
“…The Figure 7. Serum LPS levels after infusion of either saline, heat-killed S. epidermidis, 1 X 10"/kg, or heat-killed E. coli, 5.0 x 109/kg.…”
mentioning
confidence: 99%